2012
DOI: 10.1111/j.1751-2980.2012.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra‐abdominal pressure on hepatic microcirculation: Implications of the endothelin‐1 receptor

Abstract: Blocking ET(A) and ET(B) receptors partially protects sinusoidal circulation and tissue oxygenation against stress induced by high IAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Since normal portal venous pressure is between 7 and 10 mmHg, increase in intra-abdominal pressure above this level reduces portal blood flow and may therefore cause a certain degree of hepatic ischemia [ 96 – 98 ]. Animal studies have shown a pressure-dependent decrease n hepatic blood flow, although this difference was not significant in all studies [ 93 , 99 , 100 ]. Likewise, postoperative AST and ALT were significantly increased when comparing low- versus standard-pressure PNP [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since normal portal venous pressure is between 7 and 10 mmHg, increase in intra-abdominal pressure above this level reduces portal blood flow and may therefore cause a certain degree of hepatic ischemia [ 96 – 98 ]. Animal studies have shown a pressure-dependent decrease n hepatic blood flow, although this difference was not significant in all studies [ 93 , 99 , 100 ]. Likewise, postoperative AST and ALT were significantly increased when comparing low- versus standard-pressure PNP [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…decreased cardiac output, vasoconstriction in the pulmonary artery, impairment of renal and splanchnic circulation (Bomberg et al 2013 ; Ross 2012 ; Schuuring et al 2013 ). It has been demonstrated in animal experiments that dual ETA/ETB endothelin blockade during endotoxaemia improves cardiopulmonary function, reduces pulmonary hypertension and lung injury and attenuates intestinal and liver microcirculatory dysfunction (Kuklin et al 2005 ; Sánchez-Etayo et al 2012 ). Also ETA receptor blockade alone improves the function of the lungs (Mercier et al 2010 ), kidney (Rullman et al 2010 ), heart (Vanêcková et al 2005 ) and aorta (Tirapelli et al 2008 ).…”
Section: Et-1 and Endothelin Receptor Antagonists In Sepsismentioning
confidence: 99%
“…However, during carbon dioxide pneumoperitoneum, hepatic artery blood flow cannot compensate for the decrease in portal vein blood flow. One possible explanation was that the absorption of carbon dioxide through the peritoneum could lead to adrenergic activity and hypercapnia leading to acidosis, which was known to affect the regulation of hepatic perfusion (13,18). Further analysis showed that TP and ALB were decreased to a greater extent in the transperitoneal approach than that in the extraperitoneal approach.…”
Section: Discussionmentioning
confidence: 99%